Membangun Kewirausahaan dalam Menjaga Stabilitas Perekonomian Masyarakat di Desa Bukit Samang Kabupaten Majene - Galih Santoso; Dede Suparto; Ayu Rismayadi (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this community service activity is to build entrepreneurship to maintain the stability of the community's economy in Bukit Samang Village, Sendana District, Majene Regency. The methods used are: 1) contacting partners and asking for permission to carry out community service activities in the Bukit Samang Village area; 2) conducting interviews with the community around the Bukit Samang Village area; 3) asking for permission from the community around the Bukit Samang Village area and informing them that community service activities are taking place; and 4) complete all the needs to carry out entrepreneurial activities. The results of the activities that have been carried out include: 1) selling staple goods needed by the community; 2) staple goods sold are goods that last a long time and can be stored, such as garlic, shallots, crackers, nuts, and salted fish; 3) all of these staple goods were purchased in large quantities at the Palipi Market, and garlic and shallots were purchased unwashed, so we could get cheap prices; 4) cleaning shallots and garlic so consumers who buy are satisfied; 5) Weighing and packing crackers, salted fish and nuts so consumers don't have to buy in kilograms, and don't have difficulty paying those with a low economy; and 6) helping to make a cooking yeast, then packing it for sale, so that more profits are obtained. The benefits of this activity include opening up employment opportunities for mothers in Bukit Samang Village. Apart from that, mothers in Bukit Samang Village also get financial benefits that can help the family finances. The existence of community service activities can help residents around the Bukit Samang Village area to overcome economic problems during the Covid-19 pandemic, so that in economic problems the community is assisted financially.